A latent profile analysis of coping responses to individuals' most traumatic event: associations with adaptive and maladaptive mental health outcomes. Issue 6 (2nd November 2019) - Hasselle, Amanda J.; Schwartz, Laura E.; Berlin, Kristoffer S.; Howell, Kathryn H.
ABSTRACT: Background & Objectives: This study explores how empirically-derived coping response patterns influence mental health. Design: Emerging adults, currently enrolled in college and aged 18–24 ( N  = 432; M age  = 19.66; SD   = 1.65), completed self-report measures of trauma exposure, coping responses to self-selected most traumatic event (MTE), resilience, posttraumatic growth (PTG), depressive symptoms, and posttraumatic stress symptoms (PTSS). Methods: Eight coping subscales were included as indicators in a latent profile analysis. Then, associations between established profiles and mental health outcomes were examined, covarying for demographic and trauma-related variables. Results: Considering fit statistics, class size, profile patterns, and theory, the four-class model was deemed most appropriate: High Overall Coping (HCOPE; n  = 146, 34%), Low Overall Coping (LCOPE; n  = 92, 22%), High Engagement Coping (HENG; n  = 115, 27%), and High Disengagement Coping (HDIS; n  = 73, 17%). HENG participants endorsed above-average resilience and PTG, coupled with below-average depressive symptoms and PTSS. Compared to the sample average, HDIS participants endorsed lower resilience and PTG, coupled with higher depressive symptoms and PTSS. LCOPE participants endorsed low levels of all outcomes. HCOPE participants endorsed high levels of all outcomes. Conclusions: Findings suggest that clinicians who promote engagement coping and discourage disengagement coping among trauma-exposed individuals may engender the most desirable constellation of mental health outcomes.